Wells Cathedral
In the rebuilding and extension of the Norman Choir, the height of the Early English arcading was retained together with its bay spacing. Lierne vaulting of simple geometry was erected over the aisles, but the complex decorated character of the bosses, capitals and molding is more typical of the period. So, too, is the ogee arch, decorated with crockets and finials, which gives access to the choir itself.